Conflict and agricultural performance: Evidence from Myanmar - Win, Myat Thida; Maredia, Mywish K.; Jin, Songqing (International Food Policy Research Institute, 2024)
Recent years have witnessed an escalation in conflict, especially in developing countries where a significant proportion of the population relies on agriculture. It is crucial to understand how these conflicts impact agricultural production, given its importance for food security and agricultural transformation in these regions. However, research exploring how persistent conflicts affect agriculture is still nascent. Our study adds to this body of research by establishing a causal link between ongoing conflicts and their impact on paddy production, a primary staple crop in Myanmar. This analysis is based on data from a nationally representative phone survey conducted amidst active conflicts. We find that conflict adversely affects paddy production in various ways, including decreases in production and yield, as well as decreases in farmgate prices and the value of production. Our analysis reveals that conflict events, particularly those targeting civilians, have more pronounced negative effects on paddy production, yield, farmgate prices, and the value of production compared to non-targeted conflict incidents that do not purposively target civilians but could potentially disrupt input and output markets. The timing of conflict also significantly affects paddy production, with incidents occurring in mid-season, and during pre-planting and planting periods being the most damaging. Conflict leads to a decrease in the land area devoted to paddy cultivation, lowered probability and intensity of compound fertilizer usage, and an increased reliance on possibly lower quality seeds and exchange labor use. Our findings provide timely and informative insights for development partners and policy frameworks, highlighting the need for emergency assistance and intervention strategies to mitigate the impact of conflict and enhance resilience in areas vulnerable to conflict and instability.